WebGIS-Based Noise Information System in Bogor City (Case Study West Bogor Subdistrict) - Tri Permadi; Budi Susetyo; Safaruddin Hidayat Al Ikhsan (Sean Institute, 2021)
Along with the development of development in West Bogor subdistrict, there will be environmental noise that comes from these activities. Based on the Decree of the Minister of Environment No. 48 of 1996, noise is unwanted sound from a business or activity in a certain level and time that can cause human health problems and environmental comfort. Geographical Information System (GIS) is a computer-based system that has the ability to handle geographic reference data to enter, process and produce data so that it can be used as a reference in making decisions in planning. Noise measurements use a Sound Level Meter for 10 (ten) minutes for each measurement and GPS to determine the position of the location coordinates. The purpose of this study is to map the contours and distribution of noise levels and design a webgis-based noise information system in West Bogor subdistrict, Bogor City. To create a noise distribution level map using Surfer software using the kriging and Arcgis methods. Based on the measurement results, the value of the noise level ranges from 50 dB - 70 dB, because it is on the main road and comes from transportation modes. Noise information will be made into webgis display.